M.I.C.E. Tourism as a Human Resources Management Tool (Aplication Study AIESEC) - Pacáková, Kateřina; Abrhám, Josef; Havlíčková, Blanka; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The thesis describes characteristics of MICE tourism in general and in the Czech Republic. It also observes usage and process of preparation of MICE products in student organizations, namely in AIESEC Czech Republic and Student Union CTU, and presents a general eight aspect scheme for organizing such events to ensure their contribution to human resources management.
Vedoucí práce: Josef Abrhám
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: cestovní ruch a regionální rozvoj [obor bakal. práce]; bakalářské práce; bachelor's theses